Comprehending Comprehensible Input (CI): Some Observations - Jerome Moran (The Journal of Classics Teaching, 2022)
Most people who use the word ‘Latin’ as the name of a language in antiquity (not Medieval or Neo-Latin therefore) seem unaware that Latin was a continuum made up of many different varieties, Classical Latin (which they identify with Latin) being only one of them. So when they talk of spoken Latin they mean spoken Classical Latin, no other variety from antiquity being available that is suitable to be spoken. This is ironic on two counts. First, the overwhelming majority of native Latin speakers did not speak Classical Latin at all. Secondly, the small minority of people who did speak it did not do so routinely as a language of everyday conversation, but only on certain formal occasions and in certain public situations. They spoke routinely the appropriate form of their first language, the form that was used by a social, cultural and educational elite. This was not Classical Latin, which was not an acquired form of Latin but one that was learned as if it were a second language. What the language they did speak routinely was like we do not know, and no doubt it comprised several different registers, as languages do. Whether they realise it or not, people who engage in informal conversations in formal Classical Latin today are not re-enacting any authentic experience that was to be had in the ancient world.